Optimization of Microwave-assisted Extraction of Anthocyanin from Clitoria Ternatea Flowers - Izirwan, Izhab; Thurga Devi, Munusamy; Nor Hanimah, Hamidi; Siti Zubaidah, Sulaiman (International Journal of Mechanical Engineering and Robotics Research, 2020)
Currently, public awareness towards the usage of dyes and colorants from plant extracts as an alternative for synthetic colorants are increasing. Hence, the blue colour of Clitoria Ternatea flowers signifies the presence of anthocyanin which has numerous benefits. In this study, microwave-assisted extraction (MAE) of anthocyanin from Clitoria Ternatea flowers using ethanol as solvent based on the design of experiment given by response surface methodology was performed. A central composite design was applied to evaluate the optimal conditions of three process variables namely extraction temperature (°C), extraction time (min) and solid-to-liquid ratio (g/mL). The concentration of anthocyanin was analyzed using pH differential method via UV-Vis Spectrophotometer. At quadratic model of R2=0.76633, the obtained extraction yield of the blue dye was 49.97%. A validation test was carried out under critical conditions gave 48.61% of extraction yield which was closed to the predicted value of 49.36%. As for the total anthocyanin content (TAC), 0.457 mg/g of anthocyanin was obtained. In a nutshell, MAE is a viable extraction method for extracting anthocyanins from Clitoria Ternatea flowers. Thus, the use of Clitoria Ternatea extract has a potential use as an alternative source of food colorants replacing the existing synthetic dyes.